Improved charge trapping flash device with Al2O3/HfSiO stack as blocking layer - Zheng, Zhi-Wei (志威 郑); Huo, Zong-Liang (宗亮 霍); Zhu, Chen-Xin (晨昕 朱); Xu, Zhong-Guang (中广 许); Liu, Jing (璟刘); Liu, Ming (明刘) (Chinese physics B, 2011)
In this paper, we investigate an Al2O3/HfSiO stack as the blocking layer of a metal-oxide-nitride-oxide-silicon- type （MONOS） memory capacitor. Compared with a memory capacitor with a single HfSiO layer as the blocking layer or an Al2O3/HfO2 stack as the blocking layer, the sample with the Al2O3/HfSiO stack as the blocking layer shows high program/erase （P/E） speed and good data retention characteristics. These improved performances can be explained by energy band engineering. The experimental results demonstrate that the memory device with an Al2O3/HfSiO stack as the blocking layer has great potential for further high-performance nonvolatile memory applications.